2017
DOI: 10.1109/tmi.2017.2671839
|View full text |Cite
|
Sign up to set email alerts
|

Novel MRI Technique Enables Non-Invasive Measurement of Atrial Wall Thickness

Abstract: Knowledge of atrial wall thickness (AWT) has the potential to provide important information for patient stratification and the planning of interventions in atrial arrhythmias. To date, information about AWT has only been acquired in post-mortem or poor-contrast computed tomography (CT) studies, providing limited coverage and highly variable estimates of AWT. We present a novel contrast agent-free MRI sequence for imaging AWT and use it to create personalized AWT maps and a biatrial atlas. A novel black-blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
2
42
0
1
Order By: Relevance
“…The right (RA) and left atrial (LA) geometries of healthy volunteers and patients, respectively, were obtained by manual segmentation using ITK Snap. The AWT maps for all geometries were computed using previously published methods [8]. This involved the generation of epicardial and endocardial meshes from the segmentations and the computation of the AWT maps by averaging the distance between nearest nodes on corresponding meshes.…”
Section: Awt Measurementsmentioning
confidence: 99%
“…The right (RA) and left atrial (LA) geometries of healthy volunteers and patients, respectively, were obtained by manual segmentation using ITK Snap. The AWT maps for all geometries were computed using previously published methods [8]. This involved the generation of epicardial and endocardial meshes from the segmentations and the computation of the AWT maps by averaging the distance between nearest nodes on corresponding meshes.…”
Section: Awt Measurementsmentioning
confidence: 99%
“…Atrial geometries and fibrosis distributions were extracted from MRI to create 3D human atrial models, as described in previous studies ( Varela et al, 2017b ) and shown in the diagram in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, neither the influence of AWT gradients on the RD dynamics in realistic atrial geometries nor comparative effects of AWT gradients and fibrotic patches on RDs have been investigated. Reconstruction of the atrial wall from imaging ( Varela et al, 2017b ) provides basis for computational modeling of the RD dynamics in patient-specific atrial geometries, to understand the role of AWT gradients in influencing RD locations. Elucidating the relationships between AWT gradients, fibrosis, and RD locations can lead to an improved understanding of AF mechanisms, and ultimately help identify patient-specific ablation targets, improving the efficacy of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For 1 individual volunteer (subject 2), and for illustration purposes, a 3D whole-heart PSIR sequence 25 was acquired using an imaging protocol similar to that previously introduced for MRI-derived measurements of AWT. 24 Briefly, an IR pulse was applied in odd heartbeats, where data acquisition was performed with a 90° flip angle. The TI was set equal to 360 ms to null the signal from blood, as determined using a 2D TI scout scan that was acquired in coronal view.…”
Section: Data Acquisition-healthy Subjectsmentioning
confidence: 99%
“…Quantified AWT thickness amounted to 2.54 ± 0.87 mm for the right atrium and to 2.51 ± 0.61 mm for the left atrium, which is in good agreement with MRI-derived measurements previously obtained in healthy subjects (2.7 ± 0.7 mm and 2.4 ± 0.7 mm for right and left atrium, respectively). 24…”
Section: Awt Quantificationmentioning
confidence: 99%